The Chemical Optimization of Cerebral Embolectomy trial: Study protocol. Issue 1 (January 2021) - Renú, Arturo; Blasco, Jordi; Millán, Mónica; Martí-Fàbregas, Joan; Cardona, Pere; Oleaga, Laura; Macho, Juan; Molina, Carlos; Roquer, Jaume; Amaro, Sergio; Dávalos, Antonio; Zarco, Federico; et al.
Rationale: The potential value of rescue intraarterial thrombolysis in patients with large vessel occlusion stroke treated with mechanical thrombectomy has not been assessed in randomized trials. Aim: The CHemical OptImization of Cerebral Embolectomy trial aims to establish whether rescue intraarterial thrombolysis is more effective than placebo in improving suboptimal reperfusion scores in patients with large vessel occlusion stroke treated with mechanical thrombectomy. Sample size estimates: A sample size of 200 patients allocated 1:1 to intraarterial thrombolysis or intraarterial placebo will have >95% statistical power for achieving the primary outcome (5% in the control versus 60% in the treatment group) for a two-sided (5% alpha, and 5% lost to follow-up). Methods and design: We conducted a multicenter, randomized, placebo-controlled, double blind, phase 2b trial. Eligible patients are 18 or older with symptomatic large vessel occlusion treated with mechanical thrombectomy resulting in a modified treatment in cerebral ischemia score 2b at end of the procedure. Patients will receive 20–30 min intraarterial infusion of recombinant tissue plasminogen activator or placebo (0.5 mg/ml, maximum dose limit 22.5 mg). Study outcome(s): The primary outcome is the proportion of patients with an improved modified treatment in cerebral ischemia score 10 min after the end of the study treatment. Secondary outcomes include the shift analysis of the modified Rankin Scale, the infarct expansion ratio, the proportion of excellent outcome (modified Rankin Scale 0–1), the proportion of infarct expansion, and the infarction volume. Mortality and symptomatic intracerebral bleeding will be assessed. Discussion: The study will provide evidence whether rescue intraarterial thrombolysis improves brain reperfusion in patients with large vessel occlusion stroke and incomplete reperfusion (modified treatment in cerebral ischemia 2b) at the end of mechanical thrombectomy.